WAYS TO INCREASE THE ECONOMIC EFFICIENCY OF CONSTRUCTION MATERIAL PRODUCTION ENTERPRISES IN THE CONDITIONS OF THE MARKET ECONOMY - Tirkashev Orif Makhmudovich; Karjavov Zayniddin (Лучшие интеллектуальные исследования, 2024)
Abstract: This article examines the main methods of increasing the economic efficiency of enterprises producing building materials in the market economy. From technology adoption and innovation to supply chain optimization and sustainability practices, a holistic approach is critical to driving operational excellence and maintaining a competitive edge in the industry. Let's dive deeper into the strategies that help these businesses thrive in a dynamic market environment.